Maturation of the enteric mucosal innate immune system during the postnatal period. Issue 1 (July 2014) - Fulde, Marcus; Hornef, Mathias W.
Summary: The innate immune system instructs the host on microbial exposure and infection. This information is critical to mount a protective innate and adaptive host response to microbial challenge, but is also involved in homeostatic and adaptive processes that adjust the organism to meet environmental requirements. This is of particular importance for the neonatal host during the transition from the protected fetal life to the intense and dynamic postnatal interaction with commensal and pathogenic microorganisms. Here, we discuss both adaptive and developmental mechanisms of the mucosal innate immune system that prevent inappropriate stimulation and facilitate establishment of a stable homeostatic host–microbial interaction after birth.